Calculation of the phase envelope of multicomponent mixtures with the bead spring method. Issue 3 (12th October 2015) - Nikolaidis, Ilias K.; Economou, Ioannis G.; Boulougouris, Georgios C.; Peristeras, Loukas D.
Abstract : A robust numerical scheme for the calculation of constant composition (isoplethic) phase diagrams of complex multicomponent mixtures is presented. The scheme refers to the sequential calculation of the phase envelope of a mixture by guiding the estimation for the equilibrium curve via the introduction of a "spring" that sets the slope value of the modified tangent plane distance with respect to either temperature or pressure. A simple variation of the proposed method allows direct estimation of the Cricondentherm and/or Cricondenbar points, thus avoiding the calculation of the entire phase diagram. Extensive tests of the proposed scheme for different types of phase diagrams, using both cubic and higher‐order equations of state are presented. © 2015 American Institute of Chemical Engineers AIChE J, 62: 868–879, 2016